AN ANALYSIS OF INDONESIAN-ENGLISH CODE MIXING USED IN NESSIE JUDGE’S VIDEOS YOUTUBE CHANNEL - da costa, rui pedro daos; Sahan, Anselmus; Kamlasi, Imanuel ((JELE) Journal Of English Language and Education, 2021)
Mixing one language with different language, in sociolinguistics is referred to as code mixing. Considered one of social media to share the facts is YouTube. The phenomena of code blending also takes place in certainly one of YouTube channel namely Nessie Judge. Accordingly, this observe focuses on code blending occurs in Nessie decide YouTube channel. The statements of the research trouble in this observe are:(1) What are the forms of code mixing used in Nessie decide YouTube channel? (2) Why are codes mixing utilized in Nessie judge YouTube channel? The objectives of this study are:(1) To discovered the varieties of code mixing that utilized in Nessie Judge YouTube channel, (2) To find out the reasons of code mixing that used in Nessie Judge YouTube channel. In this examine, the researcher used library look at with qualitative research and the researcher as the tool of this have a look at. The item changed into Nessie judge’s YouTube channel. The information of this study changed into all of utterances that include of code mixing. The researcher collects the records use note taking technique. The result of this examine indicates:(1) The kinds of code mixing discovered in the motion pictures of Nessie Judge’s YouTube channel are: intra sentential, intra lexical, and involvement in a alternate of pronunciation, (2) The reason why codes mixing determined in Nessie judge YouTube channel are: talking about specific subject matter, being emphatic approximately something, repetition used for clarification, and expressing organization identity and unity.